Implications of sustainable agricultural intensification for family farming in Africa: anthropological perspectives - Snyder, Katherine A.; Cullen, Beth (2014)
In this paper, we will explore the ways in which sustainable intensification interventions often overlook fundamental social dynamics in rural landscapes. We provide evidence of the underlying social, political and environmental contexts that affect farmers’ land-use decisions. While there are numerous initiatives to promote a Green Revolution for Africa, many tend to be dominated by technical fixes that fail to understand rural farmers’ condi - tions or aspirations and focus narrowly on increasing productivity. These technical solu - tions rarely address the broader social, economic and political challenges to agricultural production and farmers’ livelihoods. Finally, top-down technical approaches frequently fail to build on the local knowledge, innovative capacity and expertise of farmers and members of rural communities throughout Africa. Examples from fieldwork in Ghana, Ethiopia and Tanzania are used to illustrate our arguments.